1998
DOI: 10.1109/92.711315
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the prefabricated routing track distribution on FPGA area-efficiency

Abstract: In most commercial Field-Programmable Gate Arrays (FPGAs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(3 citation statements)
references
References 12 publications
(16 reference statements)
0
3
0
Order By: Relevance
“…Betz and Rose [3,4] looked at two issues in interconnect distribution. Using at the segmented model of Figure 1(a), they considered the issue of having different channel densities in different areas of the chip.…”
Section: Uniformitymentioning
confidence: 99%
“…Betz and Rose [3,4] looked at two issues in interconnect distribution. Using at the segmented model of Figure 1(a), they considered the issue of having different channel densities in different areas of the chip.…”
Section: Uniformitymentioning
confidence: 99%
“…The routing fabric comprises horizontal and vertical segmented routing channels. In all delay and power comparisons that follow, we set the number of routing tracks to be 15% higher than the minimum required to avoid excessive routing congestion as in [2], [6]- [31]. The design of the connection box (CB) and switch box (SB) follows [2] and the design of the switch point is MUX-based as described in [32] (see Fig.…”
Section: Preliminariesmentioning
confidence: 99%
“…A set of datapath-oriented CAD tools, including synthesis, packing, placement, and routing tools, have been developed at the University of Toronto; and in this paper, these tools are used to investigate the area efficiency of the multi-bit routing architecture by experimentally determining the best granularity values and the best amount of bus-based connections for the proposed routing architecture. Extensive research [16] [17] [18] [19] [20] [21] has been conducted in the past in order to Using Bus-Based Connections to Improve Field-Programmable Gate Array Density for Implementing Datapath Circuits determine the best structures for various conventional FPGA routing architectures. These studies have shown the importance of routing architecture on the overall area-efficiency of FPGAs.…”
Section: Introductionmentioning
confidence: 99%